Nietzsche's money. (February 2013) - Dodd, Nigel
Although Nietzsche rarely features in discussions of money, he offered important insights into such matters as the relationship between the money economy and the permanent decadence of modernity, money's impact on social hierarchy and individualism and the moral economy of debt. His remarks on these themes are closely connected to two of his best known, but controversial, ideas: the eternal return and the Übermensch . In this paper, I explore how Nietzsche's arguments, and these two concepts in particular, have been taken up by three thinkers who have made distinctive and original contributions to the sociological and philosophical understanding of money, credit and debt: Georg Simmel in The Philosophy of Money (1907), Walter Benjamin in 'Capitalism as Religion' (1921), and Norman Brown in Life Against Death (1959). Nietzsche's ideas fulfil a pivotal role in each of these treatments of money: in particular, he informs Simmel's exploration of the relationship between money, individualism and socialism; Benjamin's examination of the 'guilt history' of modern capitalism and its moral economy of debt; and, finally, Brown's explorations of the roots and consequences of our neurotic money complex. Each of these thinkers puts a different complexion on Nietzsche's own thoughts regarding money, as well as his broader philosophy. Nevertheless, he provides all three thinkers with a sharply critical perspective on the idea that money's expansion in the modern world reflects the individual's liberation from traditional social ties and ancient moral bonds.